Intrinsic and Extrinsic Value in Erin Brockovich Movie Script: An Ecolinguistics Analysis - Nurfatimah Lissamustika (ELITE: Journal of English Language and Literature, 2021)
This study focused on analyzing intrinsic and extrinsic value in â€œErin Brockovichâ€ by Susanah Grant. This study aimed to describe a character's utterance that contains intrinsic and extrinsic values in Erin Brockovich's movie script. There are two sources of data in this study, they are movie scripts from Erin Brockovich's movie as primary data and audiovisual movies as secondary data. Data is collected through Searching and downloading the movie script of Erin Brockovich, reading the script, looking for sentences containing the intrinsic and extrinsic value, taking note of Intrinsic value and extrinsic value, coding the data and rechecking the data. Techniques of Data analysis are done through the presentation of data, explaining and interpreting data, and concluding data. This study indicated that the Erin Brockovich movie script has two values as intrinsic and extrinsic value. First, the intrinsic value is presented in the form of Erin's care to the people at Hinkley. Second, the extrinsic value is presented in the form of PG&E's selfish attitude towards the people at Hinckley. The writer obtained 21 data. 18 intrinsic value data and 3 extrinsic data of intrinsic value found in this movie script meaning that intrinsic value is more dominant than extrinsic value. Intrinsic value is more dominant than the extrinsic value because in this movie script the focus is more on discussing positive actions carried out by the characters in the movie that are helping people by overcoming cases of water pollution.